PENGARUH CITRA MEREK, KEPERCAYAAN DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN MIE SEDAAP INSTAN (Studi kasus di daerah Jakarta Barat) - Sari, Fifi Amelia; Muchtar, Tafiprios (Teropong : Jurnal Manajemen dan Bisnis, 2022)
The research aims to know how brand image, trust and product quality toward loyalty of consumer. Design research using quantitative assosiatif. The sample uses a judmental sampling as much as 145 mie sedaap instan consumer respondents in West Jakarta. Data analysis using structural equation modelling with Partial Least Square (PLS) version 3.2.8. the results showed that the brand image is positive and significant effect toward consumer loyalty mie sedaap instan, trust has a positive and significant toward consumer loyalty mie sedaap instan and quality product effect positively and significantly to consumer loyalty mie sedaap instan.